(untitled) - London, Jack (New York, NY, 1982)
The Selected Short Stories show that London wasn't just a Yukon guy...he had some other arrows in his quiver. A few stories demonstrate his--at the time--devout socialism, which lasted up until he himself got rich. The Apostate is the weakest of these, but The Strength of the Strong is a pretty good allegory for fin-de-siecle capitalism, with all its gory excesses. London also writes convincingly about such diverse topics as boxing, South Sea cannibals, and straight-up science fiction.
Keywords: American literature,American fiction; 19th century,19th century